Occurrence of Amblyomma integrum from wild Asian Elephant (Elephas maximus) in Tamil Nadu (India) - A report: Occurrence of Amblyomma integrum from wild —– (Elephas maximus) in Tamil Nadu (India) - A report - Kavitha, K T; Rubinibala, B; Prathipa, A; Latha, Bhaskaran Ravi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Ticks and tick-borne diseases affect animal and human health worldwide and are the cause of significant economic losses. During necropsy of a free ranging wild Asian elephant unusually large, engorged ticks attached to the ear and d ewlap was noticed. On the basis of morphological study, the ticks were identified as Amblyomma integrum. This is the first report on the occurrence of A. integrum ticks on Asian elephant of Tamil Nadu, India. The detailed morphology of the sexes and the medical and veterinary significance of the tick are discussed in the light of available literature.